2009
DOI: 10.1115/1.3068320
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Discharge and Total Temperature Increase Characteristics of the Labyrinth Seals With Honeycomb and Smooth Lands

Abstract: The viscous work generated by the rotating components of a seal not only represents a direct loss of power but also causes an increase in the total temperature of fluid (windage effect). In order to study the discharge and total temperature increase characteristics of the stepped labyrinth seals with smooth and honeycomb lands, 3D Reynolds-averaged Navier–Stokes solutions from CFX is used in this work. At first, the influences of the inlet preswirl, leakage flow rate, and rotational speed on the total temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 8 publications
3
7
0
Order By: Relevance
“…The pressure ratio π influences the windage heating: the presented correlation shows that the windage power is increased at higher pressure ratios. This is in agreement with Yan et al (2009). The reason for this behaviour is that the square of the flow velocity influences the wall shear.…”
Section: Calibration Of the Algebraic Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…The pressure ratio π influences the windage heating: the presented correlation shows that the windage power is increased at higher pressure ratios. This is in agreement with Yan et al (2009). The reason for this behaviour is that the square of the flow velocity influences the wall shear.…”
Section: Calibration Of the Algebraic Modelsupporting
confidence: 90%
“…pressure ratio, geometry, axial Reynolds number, circumferential Mach number and fluid parameters mostly influence the windage and leakage behavior. Yan et al (2009) analyze the influence of honeycomb structures, applied to the stator, on windage heating behavior numerically. The labyrinth investigated is again a stepped labyrinth with four fins.…”
Section: Current State Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD analyses, concerning labyrinth seals in both smooth and honeycomb configuration, are presented also by Yan et al [7][8][9][10][11]. The outcomes of their numerical analyses were compared with the experimental data available in the papers by Denecke et al [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also indicated that accurate measurements within such small devices are extremely difficult to complete, so that that the windage heating uncertainty was estimated to lie in the 2-30% range. Their work allowed Yan et al [7] to carry further numerical studies of stepped IAS with and without the honeycomb. Those authors have shown a good agreement of their simulations with the experiments from Denecke et al [6]; they further provided additional characterization of the seal windage heating and leakage flow.…”
Section: Previous Workmentioning
confidence: 99%